The predictive value of the neutrophil/eosinophil ratio in cancer patients undergoing immune checkpoint inhibition: a meta-analysis and a validation cohort in hepatocellular carcinoma - Xu, Yang; Liu, Yang; Han, Huimin; He, Zhen; Cao, Wei (Frontiers in Immunology, 2025)
ObjectiveThis study was conducted to determine the prognostic relevance of neutrophil/eosinophil ratio (NER) in cancer patients receiving immune checkpoint inhibition therapy.MethodsA comprehensive search of the literature was carried out across PubMed, EMBASE, and the Cochrane Library to identify relevant studies published before May 2025. Key clinical endpoints included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR). Additionally, a retrospective cohort analysis involving 67 hepatocellular carcinoma (HCC) patients who received ICIs at our center was undertaken to evaluate the prognostic significance of NER with respect to OS and PFS.ResultsThis meta-analysis incorporated 12 studies comprising a total of 1,716 patients. Higher baseline NER was consistently associated with poorer clinical outcomes, including shorter OS (HR = 1.82, 95% CI: 1.57–2.11, p < 0.001) and PFS (HR = 1.62, 95% CI: 1.34–2.97, p < 0.001), as well as lower ORR (HR = 0.50, 95% CI: 0.37–0.68, p < 0.001) and DCR (OR = 0.44, 95% CI: 0.31–0.61, p < 0.001). Complementing these findings, analysis of a retrospective cohort from our institution involving HCC patients revealed that individuals with higher NER experienced significantly worse OS (p = 0.006) and PFS (p = 0.033) when compared to those with lower NER levels.ConclusionThese findings underscore the prognostic significance of pretreatment NER in cancer patients receiving ICI therapy. Integrating NER into standard clinical evaluation may enhance risk stratification and contribute to the personalization of treatment strategies.